Social consequences of the Manila North Diversion Road, for the period 1968 to 1970 - Demerre, Julian M. (1970)
The objective of this survey has been to evaluate the social consequences of the Manila North Diversion Road. The general procedure adopted for evaluating these effects has been the observance of their time-series changes from the time it became operational in August, 1968 to June, 1970. Certain areas within the region of study we reselected for this purpose. Notes were made of the traffic trend of vehicles on the MacArthur Highway which ha been bypassed by the new facility. Results of the survey showed that the expressway has produced both favorable and nil effects. On the whole, the favorable consequences outweigh the nil consequences.
Thesis (M.S. Engineering)--University of the Philippines, Diliman.